The ankle-brachial index value in patients with purulent-necrotic complications of diabetic foot syndrome - Matviychuk, B. O.; Zaremba, V. S.; Fedchyshyn, N. R.; Tsymbala, O. P. (Modern medical technology, 2019)
Diabetes and predetermined him heavy purulent-necrotic complications is actual problem medicine today’s. It is proved that patients with diabetes have big risk to development of heart-vessel disease due to the development of atherosclerosis. Standard of diagnosis peripheral arterial disease of lower limb is finding ankle-brachia index (ABI). This method is good at definition of degree of arterial occlusion. Purpose of the study. Purpose of the work: to analyse the diagnostic capability of ABI in patients who have purulent-necrotic complications of diabetic foot. Material and methods. The prospective studies covered 218 patients. The average patients age 54,2 ± 10,3years, 45,5% of them – men. The mild form of disease was in 33,2%, moderate severity – in 45,2%, severe – in 21,6%. The duration of purulent-necrotic complications was 11,5 ± 1,2 days. Results. We have seen that 128 patients have different degrees of macroangiopathy. in patients who performed amputation at the level of the thigh of ABI was 0,41 ± 0,13; at the level of the leg – 0,59 ± 0,12. Conclusion. 1. Timely diagnosis is the basis of effective treatment of purulent necrotic complications of diabetic foot. 2. In treatment, it is necessary to take into account the indicators of ABI as the main diagnostic marker of peripheral artery disease of lower limb. 3. Definition of ABI is an objective and valuable predictive marker.